THE SEQUELAE OF COVID-19 - Carlos L Pinheiro Muniz, Janailton (Health and Society, 2023)
This is a bibliographical research based on authors who have published their works in national and international digital databases. The Coronavirus is overwhelming and has been claiming lives worldwide. However, the symptoms are not restricted to the active period of the virus that continues to manifest sequelae to a phenomenon called long COVID, in English or Post-COVID Syndrome. The general objective of this research was to carry out an exploratory study of the scientific production on sequelae of COVID-19. The results of the study are not conclusive, as we are in the midst of a pandemic in Brazil and other countries.